Entre mulheres, uma história: um olhar literário à colonização brasileira em A mãe da mãe da sua mãe e suas filhas - Oliveira, Patrícia (2019)
This study is inserted in the actions of the Research Group “Ressignificações do passado na América: processos de leitura, escrita e tradução de gêneros híbridos de história e ficção – vias para a descolonização”. It presents an analysis of the Brazilian novel A mãe da mãe da sua mãe e suas filhas (2002), by Maria José Silveira. The novel tells the story of a family along 20 generations, focusing on the female characters and how they represent the “vision from beneath”, concerning those people whose voice was always silent in the official register of History, but which had its origins in the representations of official records, such as the first Civil Code of 1916 in which married women are barred judicially, being subjugated to the husbands, if not by the paternal figure; in the Charter of the Empire (1824) and to a first condition of the Constitution of the Republic (1891), which prohibited them from voting. The historical novel by Silveira (2002) is also characterized by the fact that in her tessitura, there are trademarks of the oral record, since the family histories are recounted and recalled by women and passed on, orally, from generation to generation. The work also confronts the concepts of mixing of races and purity, revealing the fruition and promotion of new ideals and artistic/social/literary manifestations and miscegenation for the context of Latin America. The interlining entries of the novel are narratives about the History of the Brazilian society which are reread with criticism by fiction. Our intention is directed to the peculiar way in which this critical rereading is manifested in Siveiras’ novel. That fact make us search for the features of the contemporary historical novel of mediation in this novel, the most recent modality of the hybrid genre of History and fiction established by Fleck (2017). In this way, our look is set upon to confirm the possibility to classify this novel in this role by a critical analysis of it. For this, a bibliographical review is carried out concerning the relations between fiction and History established by the author once she has created a line of twenty female characters to build up her familiar saga, represented in her work. In this way, we based our study, first, on the studies about the performance of the historical novel, with support was found in works by Lukács (1997, 2000, 2011), Aínsa (1988, 1991, 2003), Menton (1993), Fleck (2007; 2011, 2014, 2016, 2017), concerning our goal to confirm Silveira's work (2002) as a contemporary historical novel of mediation. In order to carry out our study about feminist critics, we select the works by Bonnici (2007), Guerra (2004-2007) Scott (2011) e Zolin (2009).. They were used to show how representative the access of writing was to women for expanding their universe of actions and also as ways of decolonization and depatrialization. This actions of ours contribute for the decolonization objectives of the Research Group above mentioned as well as to the expectations of the line of research “Linguagem Literária e Interfaces Sociais: Estudos Comparados”. Once the analysis was done, the suggested classification of the novel was proper